Control system development for unconventional aerobatic unmanned aerial vehicle with variable incidence wing - Pham, Kim Hoan. (2010)
This final year project covers the design and development processes of control system for unconventional unmanned aerial vehicle (UAV). An aerobatic aircraft is designed to be equipped with variable incidence wing with an expectation to be able to perform both conventional aerobatic maneuvers as well as cruise to hovering transition and hovering maneuvers. It is found that unconventional variable incidence wing is effective in reduction of thrust to weight ratio and lower elevator deflection in transition to hover and hovering maneuvers. However the implementation of variable incidence wing alters the stable flight dynamics of the vehicle into unstable characteristics. By utilizing the root-locus analysis and classical approach, an augmentation control system with common PID controller is developed to enhance the flight dynamics of the vehicle.